2016
DOI: 10.1111/apa.13501
|View full text |Cite
|
Sign up to set email alerts
|

Literature review shows that fathers are still not receiving the support they want and need from Swedish child health professionals

Abstract: To provide fathers in Sweden with greater support throughout the child health field, organisational changes should be considered, as this could provide further beneficial outcomes for children, families and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 55 publications
9
104
0
Order By: Relevance
“…Additionally, the focus healthcare professionals have when giving professional support to expectant parents may leave out or include minorities, such as partners of pregnant women. Even though Sweden has been considered as one of the most gender equal countries in the world, the partners in the present study expressed that the professionals sometimes preserved traditional gender roles when talking about parenthood, for example, which is in line with earlier research [39, 40]. Therefore, partners regardless of their gender, should be visual in research concerning pregnancy and childbirth.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, the focus healthcare professionals have when giving professional support to expectant parents may leave out or include minorities, such as partners of pregnant women. Even though Sweden has been considered as one of the most gender equal countries in the world, the partners in the present study expressed that the professionals sometimes preserved traditional gender roles when talking about parenthood, for example, which is in line with earlier research [39, 40]. Therefore, partners regardless of their gender, should be visual in research concerning pregnancy and childbirth.…”
Section: Discussionsupporting
confidence: 80%
“…Still, today’s reproductive health care contributes to exclude men and put major responsibility on women, and thereby reproduce contemporary gendered norms for sexuality and reproduction. Similar gendered patterns have been found within Swedish child health care (31). This calls for a new societal approach.…”
Section: Discussionsupporting
confidence: 76%
“…Across the perinatal stages, fathers feel that midwives are often disrespectful towards them [17,18]. Fathers who reported being treated respectfully by healthcare professionals were four times more likely to describe the birth as a positive experience, as they felt that they had greater control, lower anxiety and believed their partner was safe [17]. Such findings in Sweden, considered a gender-equal society, suggests that experience of feeling excluded is likely to be experienced by fathers worldwide.…”
Section: Introductionmentioning
confidence: 91%
“…However, despite fathers attendance at births becoming more common, evidence suggests that men still do not feel welcomed by perinatal health professionals, In an analysis of 62 studies of perceptions about Swedish healthcare professionals from 2000 to 2015, Wells [17] found that fathers felt excluded at prenatal clinics and consequently unprepared for the experience of birth and fatherhood. Across the perinatal stages, fathers feel that midwives are often disrespectful towards them [17,18]. Fathers who reported being treated respectfully by healthcare professionals were four times more likely to describe the birth as a positive experience, as they felt that they had greater control, lower anxiety and believed their partner was safe [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation